Information and Communication Policy in Wartime: the Case of Ukraine - Karpchuk, Natalia (Historia i Polityka, 2022)
Information and communication policy aims to build effective, harmonious communication between all actors of the democratic process with extensive use of ICTs and direct communication. The war creates an aggressive environment, which also affects the communication processes in the information sphere of the state, in particular, there is more emphasis on information, less – on deliberation. The article examines the tools used by Ukraine’s state and non-state structures to: 1) objectively inform the citizens and avoid panic, 2) inform the world community about the war and intensify international support for Ukraine, 3) fight Kremlin fakes and convey reality to the RF citizens. The specifics of TV broadcasting in Ukraine during the war, media activity of officials, social pages and Telegram channels of ministries, the Armed Forces, the Office of the President, the Verkhovna Rada of Ukraine, public organizations fighting against disinformation and fakes are analyzed. It is found out that the chosen information and communication policy is efficient at the national level (mobilized citizens to fight for victory, reduced panic, increased awareness and criticism of fakes) and at the “western” level (international moral, financial and military support to Ukraine, sanctions against Russia). However, the work in the information space of the Russian Federation is problematic because it is exposed to fierce opposition by the objects of Russian propaganda.